PENERAPAN SISTEM INFORMASI DESA BOGATAMA BERBASIS WEBSITE UNTUK MENINGKATKAN EFEKTIVITAS PELAYANAN DAN AKSES INFORMASI MASYARAKAT - Maulana, Affan; Rinaldo Adi Pratama (Badan Pelaksana Kuliah Kerja Nyata Universitas Lampung, 2025)
Technological advances move very quickly in this era of globalization. This happened due to the rapid dissemination of information. The website is currently an effective source of information that can be used as a data collection tool because it has a global reach. The use of information technology in this case is the construction of a village website. Information about villages can be easily and quickly disseminated thanks to information technology. This system aims to make it easier to share important information about the village, such as activities or other data that has not been recorded in the documentation. Using the methods of observation, interviews, and literature studies, this website can also improve services to rural communities and promote village business results, potential, population, area, and other factors. A module from OpenSID was used to build this village information system website so that people can use village services more easily and quickly. The people of Bogatama Village hope that this information system website can improve the quality of the service delivery process